Formação Continuada On-Line para Professores de Língua Inglesa da Educação Básica do Estado do Pará: BNCC e Cultura Digital - ESPÍRITO SANTO, Cleide Oliveira do (Universidade Federal do Pará, 2024)
In The new national curriculum guidelines based on the National Common Core Curriculum (BNCC) have changed, and teachers in Basic Education need ongoing training in digital competence. This research examines the formative guidelines focused on Digital Culture competency. With preliminary studies completed, the goal is to develop and offer an online extension course for the continued professional development of English language teachers in the state basic education network of Pará, with a focus on digital culture. To accomplish this, a partnership has been established between Núcleo de Inovação e Tecnologias Aplicadas a Ensino e Extensão (NITAE2), an academic unit of PPGCIMES, and the Center for the Training of Basic Education Professionals of the State of Pará (CEFOR-PA), which enables the development of a pilot version of the I-TEACH Course. Course activities were conducted using the AVACEFOR asynchronous platform, managed by SEDUC-PA, for synchronous meetings. As part of the theoretical and methodological foundation of the course, the BNCC was used in conjunction with the guidelines in the National Base (2017, 2018), the European Framework for Digital Competence for Educators (LUCAS; MOREIRA, 2017), and authors such as Redecker (2017). Using the action research method as a method of analysis, the study is qualitative in nature. By incorporating personal experiences from the researcher’s teaching career in SEDUC-PA, this approach reshapes her perspective on the challenges of implementing BNCC in a classroom setting. A methodological framework for the proposed course was provided by Filatro’s Instructional Design guidelines (2008, 2015, 2019), which outline five phases of course implementation: (I) analysis; (II) design; (III) development; and (IV) evaluation. The validation of the proposed educational product was carried out continuously through evaluations conducted by the participating teachers themselves, indicating satisfactory results in terms of implementation and formative experience. Notable outcomes of this research include: the development of an innovative proposal for a continuing professional development course for English language teachers in the state of Pará with a focus on digital culture; a product with replicability potential for other areas of knowledge; the creation of a formative path that maps the digital culture of the BNCC to the progression areas of DigCompEdu; and the promotion of digital culture in remote contexts in Pará.